Ignition characteristics of methane-air mixture at low initial temperature - Yang, Chao; Han, Qing; Liu, Haibo; Wang, Yuanyuan; Cheng, Ran (Frontiers in Energy Research, 2023)
In this paper, FLUENT software coupled with the chemical reaction mechanism is used to study the ignition characteristics of methane-air mixtures at low temperature. Variations of the main free radical concentrations, the critical conditions for a successful ignition and the chemical reaction rate of each elementary reaction for a failure ignition are obtained, respectively. Results indicate that at the beginning of ignition, methane is consumed slowly, and the mass fraction of methane inside the flame core is not zero. The consumption of methane immediately affects the concentration distribution of carbon monoxide, which presents the opposite relationship with that of methane. Mass fractions of the intermediate products and H, O free radicals are low in the burnt zone and unburnt zone, whereas reach the maximum on the flame front. OH is not only the intermediate free radical which participates in the reaction as a chain carrier, but also the combustion product remained by the intermediate reactions. Ignition radius has a large effect on the initiation process of methane combustion. At a low temperature of 150 K, the critical radius and temperature of methane ignition are 4.6 mm and 1180 K, respectively. With an decrease in initial temperature, the critical ignition radius increases while the critical ignition temperature remains unchanged. When ignition radius is smaller than the critical value, the failed ignition of methane is caused by the termination of the elementary reactions: R8, R9, R12 and R13. However, when ignition temperature is lower than the critical value, bcause of the failed initiation of elementary reaction R1, the combustion of methane is not occurred. The numerical model and the ignition method adopted in this paper can be used to study the ignition process of methane at low temperature very well.